Simulation and design of an X-band overmoded input cavity - 吴洋 陈永东 赵德奎 (Chinese physics C, 2016)
The RF input cavity is an important component for velocity-modulating types of microwave device, providing velocity modulation and density modulation. Conventional RF input cavities, however, encounter the problem of power capacity in the high frequency band due to the scaling law of the working frequency and device size. In this paper, an X-band overmoded input cavity is proposed and investigated. A resonant reflector is employed to reflect the microwave and isolate the input cavity from the diode and RF extractor. The resonant property of the overmoded input cavity is proved by simulations and cold tests, with PIC simulation showing that with a beam voltage of 600 kV and current of 7 kA, an input power of 90 kW is sufficient to modulate the beam with a modulation depth of 3%.